﻿The Cemetery and Cultural Memory: Montreal, 1860–1900 - Watkins, Meredith (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2002)
The common conception that the cemetery is a site of memory for all who died and were buried before us is a false one. There were certain biases in who was being commemorated, a form of selectivity to the memorial process that caused a great number of people to be eroded from the landscape. The argument is based on observations from a sample of seventeen hundred individuals from the latter half of the nineteenth century in Montreal. A selection of twelve surnames from archival data includes the three main cultures present in Montreal in the nineteenth century (French Canadians, Irish Catholics and English Protestants) and allows me to reconstitute families, to identify their kinship ties and to determine their situation in life. Records from the cemeteries on Mount Royal confirm the burial of individuals from the sample. The presence or absence of these individuals in the cemetery landscapes depends on different commemorative practices influenced by religion, culture, gender, status, age and cemetery regulations.